Need Supportive Teaching Is Associated With Greater Reading Achievement: What the Philippines Can Learn From PISA 2018 - Haw, Joseph Y (Archīum Ateneo, 2021)
The Philippines participated for the first time in the Programme for International Student Assessment (PISA) in 2018. PISA 2018 focused on reading proficiency and Filipino students ranked lowest in the world. We examined whether need supportive teaching would be associated with student reading achievement using 2018 Philippine data (n = 7233). We further tested if the association is generalizable across school types and socioeconomic strata. Results revealed that need supportive teaching positively predicted student reading achievement across different types of school and socioeconomic contexts. Results suggest the potential importance of enhancing need supportive teaching as an evidence-based approach to improve students’ reading achievement. This empirical insight shows how reforms that improve teaching and learning present more significant promise in increasing reading achievement.